2008
DOI: 10.1111/j.1747-0765.2008.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and growth responses of two different salt-sensitive cucumber cultivars to NaCl stress

Abstract: The effect of NaCl stress on the growth, membrane permeability, anti-oxidant enzyme activities and ion content of cucumber seedlings was investigated. Two cultivars (Jinchun No. 2, a relatively salt-sensitive cultivar, and Zaoduojia, a relatively salt-tolerant cultivar) of cucumber were used. Shoot and root dry weights, plant height, stem diameter, leaf area and leaf number of both cultivars decreased when NaCl concentrations increased. The decreases in shoot and root dry weights and leaf area were more signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
7
29
1
5
Order By: Relevance
“…2). Zhu et al [39] found that in relatively salt-sensitive cultivar of cucumber, NaCl stress did not provoke the accumulation of free proline, whereas its content increased markedly in relatively salt-tolerant cultivar. It seems, therefore, that cultivar Polan F 1 , used in the present experiment, is relatively salt-sensitive.…”
Section: Discussionmentioning
confidence: 98%
“…2). Zhu et al [39] found that in relatively salt-sensitive cultivar of cucumber, NaCl stress did not provoke the accumulation of free proline, whereas its content increased markedly in relatively salt-tolerant cultivar. It seems, therefore, that cultivar Polan F 1 , used in the present experiment, is relatively salt-sensitive.…”
Section: Discussionmentioning
confidence: 98%
“…Porém os efeitos promovidos por essas plantas podem ser influenciados por fatores abióticos (Alcântara et al, 2000). Desta forma, para o uso de espécies como adubos verdes, especialmente em regiões áridas e semiáridas, deve-se levar em consideração a salinidade do solo, visto que este é um dos fatores ambientais mais limitantes na produtividade das culturas (Zhu et al, 2008 ).…”
unclassified
“…Altas concentrações de sais na zona radicular provocam alterações nas respostas fisiológicas das plantas (Parida & Das, 2005) como desequilíbrio no balanço osmótico, desorganização das membranas, inibição na divisão e expansão celular (Mahajan & Tuteja, 2005) características que contribuem para a diminuição do crescimento das plantas, evento passível de se manifestar em reduções em altura de planta, no número de folhas e no diâmetro do caule (Zhu et al, 2008;Silva et al, 2009;) na área foliar e na produção de fitomassa Neves et al, 2009;Santos et al, 2010).…”
unclassified
See 1 more Smart Citation
“…Salinity stress had a significant effect on growth rate of cucumber, at salinity level higher than 2.5 dS m -1 , which caused decline in yield 13% (Dorota, 1997). Therefore, cucumber has been classified as salt sensitive crop (Wang, 1998;Stepien and Klobus, 2006;Zhu et al, 2008). Between several strategies to tackle the adverse effects of salts on agricultural crops, many shot-gun approaches are used these days.…”
Section: Introductionmentioning
confidence: 99%